التصميم الانشائي لمستشفى الجنوب دير سامت بجامعة بوليتكنك فلسطين - المصري, عمر; الحروب, علاء; قزاز, محمد; قيسية, اسامة; الحروب, احمد (Palestine Polytechnic University - كلية الهندسة - مباني, 2018)
Structural Design For "AL-janoub Hospital " In Deir Samet The idea of this project can be summarized by preparing AL-janoub Hospital. Which consists of all facilities that should be available in any Hospital. The project is consists of five floors, and the total area of the building is 25820 meter square, the design of the project is based on the multiplicity of spatial cluster and distributed consistently aesthetically and functional . We used ACI-318 code and structural designing programs such, ATIR, AutoCAD (2014), and we studied some old graduation projects, and the project will include detailed structural study of identified and analysis of the construction elements and the expected various loads, and then the structural design of elements and the preparation of shop drawings based on the prepared design God grants success
CD , no of pages 99 , مباني16/2018, in the store
Keywords: التصميم, الانشائي, لمستشفى,الجنوب, دير سامت, بجامعة بوليتكنك فلسطين